Corrupted packets discarding mechanism to alleviate congestion in wireless body area network - Wan Aida Nadia Wan Abdullah; Naimah Yaakob; R. Badlishah Ahmad; Mohamed Elshaikh Elobaid; Siti Asilah Yah (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Generation of high traffic from continuous sensing and collection of medical data from various biosensors on multiple body is most likely to occur in the Wireless Body Area Network (WBAN). This could be a factor to the congestion in the network. Occurrence of congestion would collapse the performances in the WBAN network in terms of increment in delay, high packets loss, reduction in throughput and packet deliver ratio (PDR). The crucial concerns in WBAN are prevention from the loss of critical data and longer delay in the network as they could result to late delivery of medical treatment and possibility of the increase in mortality. Therefore, this study proposes a mechanism to alleviate the congestion from happening in the first place through discarding the corrupted packets before the beginning of data transmission to the base station. Extensive simulations are done in OMNeT+ to analyze the performance of the proposed mechanism by varying traffic from low to high under different number of nodes and constant Bit Error Rate (BER) and packet size. From the finding, it can be concluded that the proposed mechanism shows better performances in terms of low delay and packet loss as well as high throughput and PDR compared to typical WBAN.